Case Report: Inferior Vena Cava Agenesia in a Young Male Patient Presenting With Bilateral Iliac Veins Thrombosis - Pasqui, Edoardo; de Donato, Gianmarco; Camarri, Silvia; Molinari, Raffaele; Cascinelli, Irene; Pelini, Veronica; Abate, Luigi; Palasciano, Giancarlo (Frontiers in Surgery, 2022)
INTRODUCTION: Inferior Vena Cava (IVC) anomalies represent an uncommon finding with a prevalence of 0.3% to 0.5% of healthy patients. Specifically, the condition characterized by the agenesis of the IVC (AIVC) have been observed in a 0.0005%-1% of general population. AIVC is strongly related to deep vein thrombosis (DVT) of lower limb and pelvic district, especially in young patients. The rarity of the presented condition could relate to an underestimation of its impact on particular clinical setting leading to a delayed diagnosis and inaccurate early- and long-term management. REPORT: We present a case of this anomaly regarding a 31-years-old male patient presenting with bilateral symptomatic proximal DVT. Duplex vascular ultrasound and subsequent CT-Angiography reveal the complete occlusion of the right external and common iliac vein and a partial occlusion of the contralateral external iliac vein. The exam also revealed the interruption of IVC in its infrarenal part. At the level of renal veins coalescence, IVC appeared again in its usual position. A dilatated portal system, hepatic veins and Azygos and Hemiazygos systems were also highlighted. Anticoagulation was promptly started with the administration of Fondaparinux 7.5 mg/die, shifted towards the administration of a direct oral anticoagulant (Apixaban 5 mg twice a day) in addition, compression stocking was initiated within 24 hours from diagnosis. At 1-month follow-up Vascular Duplex Ultrasound revealed a complete resolution of the iliac veins’ thrombosis. CONCLUSION: It is important to consider the eventuality of IVC anomalies in a young adult presenting with unexplained, extensive, or bilateral DVT. Accurate diagnostic evaluation is necessary to fully identify this condition that could represent a real challenge.